Pengaruh Kepuasan Kerja Dan Pengembangan Karir Terhadap Kinerja Karyawan Pada PT Bank Syariah Indonesia Tbk Area Jakarta Saharjo - Angga Prasetia; Endang Kustini (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstrak. This study aims to determine the Influence of Job Satisfaction and Career Development on Employee Performance at PT Bank Syariah Indonesia Tbk Jakarta Saharjo Area. both partially and simultaneously. This type of research uses an associative quantitative method. The sampling technique uses a saturated sample of ninety-one respondents. Data analysis techniques use, data instrument tests, classical assumption tests, simple linear regression, multiple linear regression, correlation coefficients, coefficients of determination. Hypothesis testing uses t tests and F tests. The results of the analysis show: Work experience partially affects job satisfaction on employee performance with a simple linear regression equation Y = 25.011 + 0.399 X1. The correlation coefficient value of 0.428 means it has a moderate level of relationship and a determination coefficient of 18.3% means that performance is influenced by job satisfaction by 81.7%. This is proven by the t test obtained t count value > t table (.768 < 1.987) and is strengthened by a significant value > 0.05 (0.081 > 0.05). Career development partially has a positive effect on employee performance, indicated by the simple linear regression equation Y = 20.244 + 0.519 X2. The correlation coefficient value of 0.498 means it has a moderate relationship and the determination coefficient of 24.8% means that performance is influenced by career development by 75.2%. This is proven by the t test obtained t count value > t table (3.321 > 1.987) and is strengthened by a significance value <0.05 (0.001 <0.05). The results of the study of job satisfaction and organizational climate simultaneously on employee performance, indicated by the multiple linear regression equation Y = 17.698 + 0.188 X1 + 0.393 X2, the correlation coefficient value of 0.527 means it has a moderate level of relationship and the determination coefficient of 27.4% means that performance is influenced by job satisfaction and career development by 72.6%. This is proven by the results of the F test hypothesis test, which obtained a calculated F value > F table (16.629 > 3.10) and is strengthened by a significance value < 0.05 (0.000 < 0.05). Thus, it is proven that Ho is rejected and Ha is accepted. Keywords: Job Satisfaction, Career Development, Employee Performance.